A elaboração da viabilidade territorial para o agronegócio na região do Matopiba - Souza, Glaycon Vinícios Antunes de (2017)
The purpose of this dissertation is to understand MATOPIBA’s region transformations, in the countryside and in the cities, promoted by the recent difusion of the agribusiness in this region. MATOPIBA is composed by portions of the states of Bahia, Piauí, Maranhão and the whole state of Tocantins. The MATOPIBA agribusiness expansion is promoting a series of region alterations in modern agricultural spaces as well as in urban centers. Some of the modern agricultural spaces changes are the densification of agricultural technical objects, the specialization in commodities production, rural exodus and land conflicts; whereas, the urban centers transformations are migration, the tertiary sector specialization driven to modern countryside demands, urbanization, and the increase of inequalities. Economic activities and political actions that enable the “invention” of the region as a state tool for the agribusiness consolidation and expansion are evaluated in this dissertation. This process of expansion of the modern agricultural front in MATOPIBA is being facilitated for the agribusiness through the technical and normative densification, and the establishment of a techno-sphere and a psycho-sphere, which are produced by the agribusiness hegemonic actors as a way of making MATOPIBA become a viable and competitive space for the global scientific agriculture. In the three last decades the geographical environment in the region mentioned above has been receiving several events produced by the State and the private sector; such events are caused by contexts that are internal and external to Brazilian territory, and they enable the formation of a new agribusiness region.